Consequence of Project Integration Management Process on Success of Project In Ethiopia - Tesfaye, Tegene; Kant, Shashi (Journal Research of Social Science, Economics, and Management, 2024)
The objective of this investigation was to examine the consequences of the project integration management process on success of project in west guji zone road construction. This research employed descriptive and explanatory research design with quantitative and qualitative research approach. Both probability and non-probability sampling techniques were applied to select a sample of 250 respondents. From probability sampling stratified sampling and simple random were used to categorize heterogeneous people into strata. Also purposive sampling was used from non-probability. The primary data were collected through well-organized questionnaires. Data was analyzed using both descriptive and inferential analysis. Descriptive data was expressed by average, mean and standard deviation. Inferential data were analyzed by regression, association with the aid of statistical tool SPSS version 20. The finding of the investigation indicates that project initiation, project planning, and project closure have positive and significant consequence on project success. However, project execution, project monitor and controlling have positive and insignificant consequence. The researcher suggests that Dudgadewa and Melka soda districts have to give first for project initiation, project planning, and project closure to improve the success of road construction. Furthermore, other researchers have to conduct investigation by taking project execution and controlling in west guji zone.